Nanogenerator Neuromodulation to Enable Locomotion Rehabilitation for Spinal Cord Injury via Epidural Electrical Stimulation - Cong Li; Yizhu Shan; Shihao Zheng; Puchuan Tan; Yuan Bai; Engui Wang; Lingling Xu; Ruizeng Luo; Shengyu Chao; Jing Huang; Pengyu Ren; Zhou Li; et al. (Advanced Science, 2025)
Abstract Spinal cord injury (SCI) is a severe neurological disease, often accompanied by impaired lower limb motor function and muscle atrophy. Epidural electrical stimulation (EES) has been demonstrated promising for SCI therapy in ways of rehabilitation by facilitating the recovery of lower limb motor abilities. However, EES necessitates a considerable consumption of electrical energy and exhibits large individual differences in treatment. Nanogenerators (NGs) based on a novel power generation technology, are capable of transforming mechanical energy into electrical power. This mechanic‐driven electrical stimulation has been reported effective in several types of neuromodulations, but not in EES to enable SCI rehabilitation. This study explores the efficacy of a hybrid‐NG (H‐NG) to elicit hindlimb locomotion in rats via EES on the spinal cord, in comparison with a commercial stimulus generator (SG). The results reveal that H‐NG can activate the spinal cord and induce hindlimb locomotion with much lower electrical parameters and much smaller individual differences than SG. In addition, benefiting from the miniature size of the H‐NG, an implantable EES system is constructed in vivo, enabling a self‐driven and rational‐controlled EES pattern. The proposed H‐NG‐based EES system provides a new strategy for optimized and personalized treatment for SCI patients.